Analyzing the Impact of Cash Position and Return On Equity on the Dividend Payout Ratio in Consumer Goods Companies Listed on the Indonesia Stock Exchange, 2019-2023 - Suka, Charisma Kuriata Ginting (Golden Ratio of Data in Summary, 2024)
company's cash position is an essential factor in determining the dividend. Return on equity, known as own capital profitability, measures the ratio of net profit after tax to the company's own capital. The dividend payout ratio measures the ratio of dividends to earnings for the company. This research population consists of 37 consumer goods industry companies listed on the Indonesia Stock Exchange in 2019-2023. Purposive sampling was used, so the sample size in this study is 18 companies. The research concludes that the cash position and the return on equity affect the dividend payout ratio.